Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Melalui E-Commerce : (Studi Kasus Pembelian Melalui Sosial Media Tik Tok) - Seldya Vindi Mayce; Risma Riski Ramadani; Riska Nuvia Cahyani; Teralia Anataya (Amal Insani Foundation, 2023)
The issue of consumer protection in e-commerce is an important aspect to pay attention to because some cases of e-commerce will place consumers in a weak or disadvantaged position. Therefore, this study aims to find out whether the consumer protection law no.Eight of 1999 can protect consumers in making transactions through e-commerce and how legal protection is for consumers in transactions through e-trade social media tik tok. This research uses normative legal methods and legal approaches and case studies. From the research it can be seen that (1) Based on Law Number 8 of 1999 concerning Consumer Protection it states that business actors are responsible for providing compensation for damage, pollution and/or losses suffered by consumers as a result of consuming traded goods and/or services. It has been clearly explained here that UUPK adheres to the principle of absolute responsibility (strict legal responsibility), in which business actors must be responsible in line with the principle of responsibility adopted by UUPK, namely absolute responsibility (strict legal responsibility). (2) Legal protection given to consumers who transact through Tik Tok is provided in the form of government regulations where every market platform company in Indonesia, including Tik Tok, is required to provide a special merchant account, this is done to make it easier for the government to track online merchant records. Tik Tok has implemented these regulations by providing Tik Tok commercial enterprise features. Thus, in carrying out e-commerce transactions, consumers are expected to be more careful and choose shops on social media carefully and thoroughly.